The Crusades Uncovered - Boas, Adrian J. 1952- (Past Imperfect, 2022)
Adrian Boas, an archaeologist with four decades' experience in the field, takes a fresh approach to investigating the experiences of crusaders, pilgrims, and settlers in the crusader states during the twelfth and thirteenth centuries. The book opens up the experience of medieval travel and crusading by drawing on personal reflection and comparison with contemporary events. Topics covered include wonderment at the strangeness of the East, adjusting to life in the Levant, the horrors of warfare, the drama of fortress and battlefield, and the theatrical beauty of religious architecture, together with new perceptions of a selection of characters known and less-known. The book encourages the reader to think more deeply as to the meaning of the topics involved